PELAKSANAAN PERLINDUNGAN HUKUM OLEH LEMBAGA PERLINDUNGAN ANAK PROVINSI RIAU TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DI WILAYAH KOTA PEKANBARU - Situngkir, Robin Fernando; Firdaus, Emilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In the protection of human rights, children are also included. A child is a person who is not yet 18 (eighteen) including a child still in the womb. Talking about the child, not apart from the mischief done by the child or in the Child Protection Act is also called Children in Conflict with the Law. In Indonesia there is an independent State institution whose function is to protect and improve the welfare of children, the institution is the Indonesian Child Protection Institution, while for the province of Riau is the Child Protection Agency of Riau Province. Based on data obtained from the Riau LPA on the issue of legal protection of children in conflict with the law in Pekanbaru City, many cases of children in conflict with unlawful laws in the LPA and the case of children who sexually harassed former sexual victim. The purpose of writing this thesis, namely First, To know Implementation of Legal Protection by Child Protection Agency of Riau Province to children in conflict with the Law in Pekanbaru City Region, Second, To know the obstacles encountered from the Implementation of Legal Protection by the Child Protection Agency of Riau Province to children In conflict with the law in Pekanbaru City Area, Third to know the efforts made to overcome obstacles from the implementation of legal protection by child protection agencies of Riau Province against children in conflict with the law in Pekanbaru City Area.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied to provide a complete and clear picture of the problem under study, while the data collection techniques in this study conducted by interviews, literatureFrom the results of research problems there are two main things that can be concluded. Firstly, the implementation of legal protection conducted by LPA Riau on children in conflict with the law in Pekanbaru City Area is in the form of penal and non penal efforts such as monitoring and accompanying children while taking the court, monitoring and assisting children in the recovery process both psychologically and socially By a psychologist. Second, the obstacles faced by LPA Riau from the implementation of legal protection by LPA Riau against Children in Conflict with the Law there are 2 (two) factors are internal factors and external factors. Suggestion Writer, First, In providing legal protection LPA Province of Riau is expected to continue to maximize preventive effort and effort of repressive that right. Secondly, LPA Riau needs to fix internal factors and external factors.Keywords: Legal Protection - Institute for Protection of Children in Conflict with the Law.